WRONGFUL LIFE CLAIMS UNDER SOUTH AFRICAN LAW: AN OVERVIEW OF THE LEGAL FRAMEWORK - Chrizell Chürr (Obiter, 2015)
Is there any probability that life can be an injury? This is a piping-hot debate among lawyers, doctors, academics, theologians, philosophers, and all affected as well as interested parties. Wrongful birth and wrongful life claims are often challenged all over the world. It is important to draw a clear distinction between wrongful birth and wrongful life claims. Wrongful birth claims are defined as prenatal negligence claims brought, by the parents of a child who is born with birth defects or abnormalities, against a doctor who negligently failed to identify, diagnose, or inform the parents of the child about possible birth defects or abnormalities. By contrast, wrongful life claims are defined as prenatal negligence claims that are brought on behalf of the child who is born with birth defects or abnormalities, against a doctor who negligently failed to identify, diagnose, or inform the parents of the child about possible birth defects or abnormalities. The core of both claims is that, were it not for the misconduct of the defendant (the doctor), the child would not have been born. Moreover, the existence of wrongful birth claims can be based on two realities, namely medical and legal realities. The medical reality relates to the existence and presence of modern, state-of-the-art technology that enables doctors to identify and diagnose children with birth defects or abnormalities before birth. The legal reality is that such claim would make no sense and would be impossible without lawful access to termination of the pregnancy (that is, abortion) – otherwise, how could the wrongful birth have been prevented? In South Africa, if parents are informed that there is a possibility that their child will suffer from a serious medical condition or a congenital disability (birth defects or abnormalities), the mother has a choice not to give birth to the child and to terminate the pregnancy in terms of section 12(2)(a) of the Constitution and under the Choice on Termination of Pregnancy Act 92 of 1996. This means that wrongful birth claims under South African law are possible, since the parents of a child born with birth defects or abnormalities are entitled to claim patrimonial damages in circumstances where a doctor negligently failed to give the necessary medical advice. However, the position regarding wrongful life claims is different, and South African law has denied any wrongful life claims, which means that a child, after being born with birth defects or abnormalities, cannot institute a claim based on wrongful life. Wrongful life claims are a controversial issue, not only in South Africa, but also worldwide; hence the aim of this analysis is, firstly, to give an overview of current case law in South Africa, and of how wrongful life claims are currently dealt with. Thereafter, the most recent case, H v Fetal Assessment Centre, will be discussed, as well as the different schools of thought, the positions in England, Germany and the Netherlands, and some possibilities as to what the situation pertaining to wrongful life claims may be when the High Court decides on the recognition or non-recognition of wrongful life claims.